KONSEP PENDIDIKAN KARAKTER DALAM PRESPEKTIF AL-QUR’AN DAN SURAH QAF - Yanto, Yanto; Fauzan, Umar; Malihah, Noor (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This article examines the concept of character education in Surah Qaf using a thematic interpretation approach. Four commentaries, namely Ibn Kathir, al-Misbah, al-Azhar, and al-Munir, are utilized as data sources. The analysis conducted is content analysis. The findings of this interpretive study indicate that human character is divided into two categories: good (muttaqin) and bad (ghaflah), as mentioned in Surah Qaf. The surah contains 30 verses that illustrate various values of character education, including religious character, independence, and integrity. The process of instilling character is revealed through verses of supervision, guidance, evaluation, punishment , and reward.